Forberedende Forsøg for Opbevaring af Is og Sne, Foredrag, den 10de Marts 1875. - Fjord, N. J. (Tidsskrift for Landøkonomi, 2018)
Forberedende Forsøg for Opbevaring af Is og Sne, Foredrag, den 10de Marts 1875.